2019
DOI: 10.1186/s12882-019-1367-1
|View full text |Cite
|
Sign up to set email alerts
|

Coronary calcification as a predictor of cardiovascular mortality in advanced chronic kidney disease: a prospective long-term follow-up study

Abstract: Background Patients with advanced chronic kidney disease (CKD) exhibit higher prevalence of coronary artery calcification (CaC) than general population. CaC has been proposed as a risk factor for mortality in end-stage CKD, but most studies in the field are based on short-term follow-up. Methods We conducted a cohort, 10-year prospective longitudinal study of consecutive cases referred to the renal unit. A non-enhanced multislice coronary computed tomography was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…Alcohol also reduces hyperglycemia through the inhibition of hepatic gluconeogenesis, with a resulting reduction in plasma glucose levels [38]. Chronic kidney disease (CKD) has shown to be associated with atherosclerosis [39,40]. Although few studies have suggested a harmful association between alcohol consumption and CKD, our study found no such association [41,42].…”
Section: Potential Mechanismscontrasting
confidence: 60%
“…Alcohol also reduces hyperglycemia through the inhibition of hepatic gluconeogenesis, with a resulting reduction in plasma glucose levels [38]. Chronic kidney disease (CKD) has shown to be associated with atherosclerosis [39,40]. Although few studies have suggested a harmful association between alcohol consumption and CKD, our study found no such association [41,42].…”
Section: Potential Mechanismscontrasting
confidence: 60%
“…The presence of vascular calcification (VC) is highly associated with an increased risk of cardiovascular disease and all-cause mortality [1][2][3]. Patients with advanced age, diabetes mellitus (DM), and chronic kidney disease (CKD) are at risk for VC.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple pathophysiological explanations have been proposed in favour of a causal link underlying the adverse cardiovascular profile of CKD patients [1,24]. These include increased intravascular calcium phosphate deposition and coronary artery calcification, [25][26][27] arterial stiffness, enhanced coagulability, endothelial dysfunction, increased subclinical inflammation, [28] volume overload [29], and left ventricular remodeling and dysfunction [30,31]. In addition, patients with CKD undergoing percutaneous coronary intervention for an acute coronary syndrome have been shown to have less complete revascularization, a condition associated with a poorer prognosis [32].…”
Section: Discussionmentioning
confidence: 99%